The impact of serum uric acid on biological aging and mortality risk: insights from the NHANES and CHARLS cohorts - Zhao, Cong; Zhao, Leying; Liu, Yang; Sun, Li-qiao; Li, Xin-rong; Wang, Yaoxian; Sun, Weiwei (Frontiers in Nutrition, 2025)
BackgroundSerum uric acid (SUA), a byproduct of purine metabolism, exerts both antioxidant and pro-inflammatory effects, making its role in aging and chronic diseases a subject of ongoing debate. Despite this, the mechanisms by which SUA influences the aging process remain poorly understood.MethodsWe analyzed data from the NHANES (1999–2010) and CHARLS (2011–2015) cohorts to investigate SUA’s impact on biological aging. Generalized linear regression models assessed SUA’s effect on biological aging markers [ΔKDM-BA, ΔPhenoAge, and allostatic load (AL)], while Cox regression models estimated its association with all-cause and premature mortality. Dose–response relationships between SUA levels and aging markers (ΔKDM-BA, ΔPhenoAge, and AL), as well as all-cause and premature mortality, were evaluated using restricted cubic splines (RCS).ResultsIn both cohorts, elevated SUA levels were significantly associated with accelerated aging. In the NHANES cohort, for each 1 mg/dL increase in SUA, ΔKDM-BA increased by 0.52 years (95% CI: 0.43–0.61, p < 0.0001), and AL increased by 0.38 (95% CI: 0.29–0.47, p < 0.0001). In the CHARLS cohort, SUA was similarly linked to an increase in ΔKDM-BA by 0.65 years (95% CI: 0.57–0.74, p < 0.0001) and AL by 0.15 (95% CI: 0.12–0.18, p < 0.0001). RCS analysis revealed a nonlinear association between SUA and ΔKDM-BA in NHANES, with a more pronounced acceleration of aging when SUA levels exceeded 4.16 mg/dL (nonlinear p < 0.0001). In CHARLS, SUA showed a nonlinear relationship with ΔKDM-BA (nonlinear p = 0.01). Additionally, in NHANES, SUA levels were associated with increased all-cause (HR: 1.04, 95% CI: 1.01–1.07, p = 0.01) and premature mortality (HR: 1.06, 95% CI: 1.00–1.13, p = 0.046). RCS analysis further demonstrated a U-shaped nonlinear relationship between SUA levels and both all-cause and premature mortality. In contrast, SUA did not show a significant association with mortality outcomes in the CHARLS cohort.ConclusionElevated SUA is associated with accelerated biological aging in both U.S. and Chinese populations, but its link to mortality was evident only in the NHANES cohort. These findings highlight SUA as a potential aging marker and call for further population-specific investigation.